2020
DOI: 10.1590/0102-33062019abb0110
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of plant use in religious offerings in Bali (Indonesia)

Abstract: Balinese Hinduism has incorporated local animistic traditions and offerings, which play a key role in the religious ceremonies called "five holy ceremonies" or Panca yadnya. Since plants constitute fundamental elements of these offerings, we aimed to contribute to their knowledge. We analyzed plants used during ceremonies by interviewing key informants in four ancient villages of Bali (Bali aga). We identified exclusive and common species associated with different kinds of ceremonies and assessed whether there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…Twenty (39%) species were found growing in the home garden, 15 (29%) species in farmland, and 13 (26%) species occurred in both the home garden and farmland, and 3 (6%) species purchased from the traditional market. The number of species recorded in this study (51 species) was comparable to the 50 ritual plant species reported in Bandung, Indonesia (Iskandar and Iskandar 2017), but lower than that in Bali, Indonesia, i.e., 125 species (Sujarwo et al 2019) and 60 species in East Nusa Tenggara, Indonesia (Sada and Jumari 2018). However, it was higher than the 36 ritual plant species reported in the Banswara district, India (Rana et al 2016), in Jambi, Indonesia, i.e., 32 species (Hariyadi and Ticktin 2012), in Yunnan Province, Southwest China, i.e., 32 species (Geng et al 2017), in Nigeria, i.e.…”
Section: Floristic Composition Of Ritual Plantssupporting
confidence: 69%
“…Twenty (39%) species were found growing in the home garden, 15 (29%) species in farmland, and 13 (26%) species occurred in both the home garden and farmland, and 3 (6%) species purchased from the traditional market. The number of species recorded in this study (51 species) was comparable to the 50 ritual plant species reported in Bandung, Indonesia (Iskandar and Iskandar 2017), but lower than that in Bali, Indonesia, i.e., 125 species (Sujarwo et al 2019) and 60 species in East Nusa Tenggara, Indonesia (Sada and Jumari 2018). However, it was higher than the 36 ritual plant species reported in the Banswara district, India (Rana et al 2016), in Jambi, Indonesia, i.e., 32 species (Hariyadi and Ticktin 2012), in Yunnan Province, Southwest China, i.e., 32 species (Geng et al 2017), in Nigeria, i.e.…”
Section: Floristic Composition Of Ritual Plantssupporting
confidence: 69%
“…This study also found that the patients in the intervention group were showing a significant change in the specific diet domain score. This result could be associated with the Balinese cultural background, where there are various local events and activities that use fruits as the primary food items for material offerings (Adiputra, 2017;Sujarwo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The flower of Hibiscus has a strong cultural value, for example in ceremonial use, etc. (Sujarwo et al, 2020). Due to the ease of propagation via cuttings, the species.…”
Section: ) Propagation Trials and Conservationmentioning
confidence: 99%